(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Marketing pre-construction (indent) housing units for the upper-middle class is often hindered by inadequate 2D brochure visuals. This study aims to implement the Multimedia Development Life Cycle (MDLC) method in designing a 3D exterior walkthrough animation as an interactive marketing tool for De Sapphire Housing. This research is a development study (Research and Development) using the MDLC model, which includes the stages of concept, design, material collection, assembly, testing, and distribution. Data analysis is carried out descriptively and quantitatively through an Alpha test to evaluate the technical feasibility of the product and a Beta test using a Likert scale questionnaire to measure feasibility based on user responses. The Alpha test results confirmed that the Full HD video output with a duration of 1 minute 48 seconds is valid without functional issues. Beta testing with marketing respondents and potential consumers resulted in an average score of 4.57 out of 5.00 (Very Feasible). This 3D walkthrough animation has proven effective in overcoming the visual limitations of 2D brochures, enhancing the consumer’s spatial experience, and potentially boosting sales conversions significantly.